2019
DOI: 10.1039/c8nr07088a
|View full text |Cite
|
Sign up to set email alerts
|

Angle-resolved photoelectron spectroscopy and scanning tunnelling spectroscopy studies of the endohedral fullerene Li@C60

Abstract: Angle-resolved photoelectron spectroscopy and scanning tunnelling spectroscopy studies of the endohedral fullerene Li@C 60 .Gas phase photoelectron spectroscopy, TD-DFT calculations and low temperature UHV STM experiments are combined to provide information about the infl uence of the encapsulated Li on the symmetry and energetics of the low lying diff use Super-Atom Molecular Orbitals (SAMOs) of Li@C 60 . PAPER Yao Cai, Yongxin Pan et al. Positive magnetic resonance angiography using ultrafi ne ferritin-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 46 publications
4
39
0
Order By: Relevance
“…A displacement to the left of the LDOS spectra indicates an electron-conducting (n-type) semiconductor, meanwhile a displacement to the right indicates hole conducting (p-type) semiconductor behavior, with the specific HOMO and LUMO levels located at negative and positive bias voltage, respectively [16,21,22]. By using a cross-sectional scanning tunneling microscope (XSTM) in UHV, Shih et al [16] reported an E g = 2.3 eV for PCBM (TA = 150 • C) with HOMO and LUMO levels located at −1.6 V and 0.7 V, respectively; from Figure 4c, the HOMO level is located at −1.65 V and the LUMO level at 0.76 V for PCBM (TA = 120 • C) leading to an average E g = 2.1 eV, which is consistent with the literature reports [16,34]. Average energy levels from Figure 4c are plotted in Figure 4d.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A displacement to the left of the LDOS spectra indicates an electron-conducting (n-type) semiconductor, meanwhile a displacement to the right indicates hole conducting (p-type) semiconductor behavior, with the specific HOMO and LUMO levels located at negative and positive bias voltage, respectively [16,21,22]. By using a cross-sectional scanning tunneling microscope (XSTM) in UHV, Shih et al [16] reported an E g = 2.3 eV for PCBM (TA = 150 • C) with HOMO and LUMO levels located at −1.6 V and 0.7 V, respectively; from Figure 4c, the HOMO level is located at −1.65 V and the LUMO level at 0.76 V for PCBM (TA = 120 • C) leading to an average E g = 2.1 eV, which is consistent with the literature reports [16,34]. Average energy levels from Figure 4c are plotted in Figure 4d.…”
Section: Resultssupporting
confidence: 90%
“…• C (open blue diamonds), show a better energy match, which could facilitate the charge transfer between D-A and be manifested as an improvement in the charge extraction [34,35] and, in an enhanced PV device performance.…”
Section: Resultsmentioning
confidence: 99%
“…Laser-desorption FTICR mass spectrometry of the starting material in both the positive and negative mode showed only minor traces of C 60 with the non-fullerene content being predominantly the stabilising anions and solvent residues. As we have shown previously [8,9] neutral Li@C 60 is evaporated from the oven along with impurities and some C 60 . The material is typically heated to a temperature of ca.…”
Section: Methodsmentioning
confidence: 60%
“…The material is typically heated to a temperature of ca. 590 K for at least 20 h to remove solvent residue and other impurities before gas phase experiments such as photoelectron spectroscopy [8] are carried out. The neutral species are ionised with an ultrashort pulse laser in the extraction region of a simple linear Wiley-MacLaren time-of-flight mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation